Electrocardiographic Changes in Scuba Divers: A Quasi-Experimental Study in Iran - ZiaZiabari 1, Seyyed Mahdi; Asadi 1, Payman; Shakiba 2, Maryam; Habibi 3, Alireza; Shokrollahi 3, Asghar; Seidshekan 4, Jabar; Noyani 5, Amir; Tavakoli 1*, Ilnaz (Shahroud Journal of Medical Sciences, 2019)
Background: Cardiac arrhythmias, conduction abnormalities, congenital and acquired heart disorders could threat the human life in scuba diving. This study purpose was to investigate and analyze the electrocardiographic changes in scuba divers. Methods: This quasi-experimental study was accomplished on scuba divers of saltwater in the Persian Gulf. Electrocardiogram (ECG) was taken during 10 min before, immediately and also by passing 60 min from diving. All ECGs were interpreted by an emergency medicine specialist regarding heart blocks, sinus arrhythmia and the heart rate changes, QT and PR intervals, QRS complex, ST segment and T wave. All statistical analyses were performed using SPSS software ver19. Significant level was set at 0.05. Results: 37 males with the mean age of 35.7±4.27 years old were enrolled in this study. There was observed no significant change in the mean of the heart rate, mean of the QT interval and T wave change between two age groups cases (<35 and >35 years old), BMI groups (<25 and >25 kg/m2), depth of water groups (<25 and >25 m) and water temperature groups (14 to 15 and 16 to 17 ̊C), in the studied time periods (p value>0.05, in all of the cases); but the mean of the pulse rate, mean of the QT interval and T wave change indicated significant difference between the studied time periods (p value=0.005, 0.001 and 0.001, respectively). Conclusions: This study indicated significant changes in pulse rate, QT intervals and T waves between studied periods in scuba divers; consequently, special attention to these changes is required.